2015
DOI: 10.3109/0284186x.2015.1061690
|View full text |Cite
|
Sign up to set email alerts
|

Dose painting by numbers in a standard treatment planning system using inverted dose prescription maps

Abstract: background. Dose painting by numbers (DPBN) is a method to deliver an inhomogeneous tumor dose voxel-by-voxel with a prescription based on biological medical images. However, planning of DPBN is not supported by commercial treatment planning systems (TPS) today. Here, a straightforward method for DPBN with a standard TPS is presented. Material and methods. DPBN tumor dose prescription maps were generated from 18 F-FDG-PET images applying a linear relationship between image voxel value and dose. An inverted DPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Such tailored treatment will be easier to implement for a continuous tumor region than for more scattered clusters [20]. Voxel clusters related to locoregional relapse would be most relevant to use for dose painting, as such clusters would indicate radiotherapy-resistant areas in the tumor [19].…”
Section: Discussionmentioning
confidence: 99%
“…Such tailored treatment will be easier to implement for a continuous tumor region than for more scattered clusters [20]. Voxel clusters related to locoregional relapse would be most relevant to use for dose painting, as such clusters would indicate radiotherapy-resistant areas in the tumor [19].…”
Section: Discussionmentioning
confidence: 99%
“…DPbN essentially establishes a mathematical link between imaging parameters and dose prescriptions that optimise chosen clinical endpoints [4,5]. The majority of DPbN studies assumed a linear relationship between image intensity and the required boost dose [24][25][26][27][28]. The linear function usually extends from a minimum dose, typically set to the current clinical dose prescription, and a maximum dose, set to a value that is considered "safe" for the target (Figure 2).…”
Section: Deriving the Desired Dose Prescription From Voxel-level Infomentioning
confidence: 99%
“…A major drawback of DPbN studies is the use of arbitrarily-chosen functions that have not been validated against clinical outcomes data [24,25,29,[31][32][33][34]. They are likely to be an oversimplification of the complex tumour dose-response.…”
Section: Deriving the Desired Dose Prescription From Voxel-level Infomentioning
confidence: 99%
“…For head and neck cancer it has in several studies been shown that increasing standardized uptake values (SUV) from 18 Ffluorodeoxyglucose positron emission tomography ( 18 FDG-PET) correlate with an increased recurrence risk after RT [2][3][4][5][6][7]. As noted in a review by Bentzen and Grégoire [8], the simplest image based dose prescription is an ad hoc linear mapping of image data into doses within suitable dose ranges, as used in several planning studies [9][10][11][12][13][14][15][16][17][18][19]. However, the same reviewers stated that the dose prescription ideally should be based upon empirical observations of pre-RT functional image data with post-RT dose-responses.…”
Section: Introductionmentioning
confidence: 99%